The Urgency Of Understanding Taxonomy In Learning Biology: (Urgensi Pemahaman Taksonomi Dalam Pembelajaran Biologi) - Pangsuma, Nisa; Hidayat, Topik (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The understanding of taxonomy is the knowledge surrounding the scope of taxonomy. Taxonomy is a discipline that studies the level of a living being. The understanding of taxonomy that originally existed in the 2013 curriculum is not listed in the Merdeka curriculum. This study aims to review how important understanding of taxonomy is in biological learning. The study used literature study methods based on relevant journals and books. An understanding of taxonomy supports knowledge in advanced Biology materials. Taking into account the prerequisite knowledge of biology in some advanced biology material understanding of this taxonomy is something important. Therefore, having an understanding of taxonomy is important in learning biology. This study underscores the urgency of understanding taxonomy in biological learning. Key Word: Taksonomi, Teaching’s Urgently, Biology learning